Social, economic, and institutional configurations of the industrial symbiosis process : a comparative analysis of the literature and a proposed theoretical and analytical framework - Faria, Emília de Oliveira (2021)
This paper aims at comparatively analyzing the IS process in three remarkable empirical cases. Ostrom’s Institutional Analysis and Development framework and its categories for analysis are used to understand each process. A theoretical and analytical framework is proposed based on a survey of contextual elements that shaped the behavior of organizations towards Industrial Symbiosis practices. The results show that although there was no clear, linear order in which the actors developed symbiotic relationships, the decisions related to Industrial Symbiosis are shaped by a similar set of variables. These variables range from technical and economic aspects, such as the diversity of industries and the viability of exchanges, to social and institutional aspects, encompassing critical environmental issues; bilateral agreements; collective engagement; trust to build cooperative relationships; communication and information sharing strategies; integrated regulatory framework at three levels; congruence between government and company actions to create a cooperative environment; and governance structures involving local government, companies, research and development institutions, and a coordinating entity or the champion. This framework may serve as a reference for diagnostic analyses assessing aspects that can be improved wherein Industrial Symbiosis is already underway. It may also be useful in prescriptive analyses assessing the potential for implementing IS.